Semantic Analysis of Poetry in Ibnu Katsir's Exegesis and Its Learning in Islamic Boarding School - Ade Nandang; Heri Khoiruddin; Jenal Bustomi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study explores the utilization of poetry in Ibn Katsir's tafsir riwayah and its instructional methods at Miftahul Huda Manonjaya Islamic boarding school in Tasikmalaya. Employing a qualitative approach, precisely the analytical descriptive research method, the research delves into integrating poetry in Ibn Katsir's exegesis and its pedagogical implementation in the mentioned Islamic boarding school. The findings reveal that Ibn Katsir employed poetry to interpret one hundred and eleven verses, highlighting the substantial role of poetic expression in his approach to tafsir riwayah. The study categorizes Tafsir learning at the pesantren into formal and non-formal learning. Seven formal learning methods are identified: lecture, question and answer sessions, demonstration, drill, problem-solving activities, recitation, and discussions. Simultaneously, non-formal learning comprises five methods: wetonan (traditional Javanese calendar-based activities), sorogan (group recitation), muhawarah (dialogue), mudzakarah (group discussion), and majlis ta'lim (religious study sessions). In conclusion, this study contributes to understanding poetry's role in Ibn Katsir's tafsir riwayah. It elucidates the diverse instructional methods applied in Tafsir learning at Miftahul Huda Manonjaya Islamic boarding school. Integrating formal and non-formal methods underscores the comprehensive educational approaches to impart Islamic knowledge in the pesantren environment. Recommendations for future research include exploring the impact of specific poetic elements on students' learning outcomes and evaluating the effectiveness of integrating technology into Tafsir teaching at Islamic boarding schools.